Experiencing a significant win and its sociodemographic and motivational predictors: A comparative analysis of pure-chance gamblers from Poland and France - Lelonek-Kuleta, Bernadeta; Bartczuk, Rafał P.; Tovar, Marie-Line; Benoit, Emmanuel; Costes, Jean-Michel (PLOS ONE, 2022)
Research on the relationship between wins and gambling behavior often focuses on winning considerably large amounts of money. It seems, however, that it is not the amount of the win, but the significance that the player assigns to the win, that exerts a decisive influence on gambling behavior. Therefore, in this study we adopted the concept of significant win: a win perceived by gamblers as important to them. The research aimed to discover what kind of wins are experienced as significant and what factors explain experiencing wins as significant. This study, conducted in Poland (N = 3,143) and France (N = 5,692), also had a comparative goal: discovering intercultural differences in experiencing significant wins. A computer-assisted web survey was administered to gamblers who engaged in pure-chance gambling, where the participant does not influence the outcome of the gamble after the initial bet is placed—selected from representative samples in both countries. We used logistic regression models to examine predictors of significant win experience in both countries and the differences between the countries. The results demonstrated that Polish gamblers more frequently considered a win significant when it was accompanied by strong, often negative emotions and was higher in monetary value normalized in terms of average monthly personal income, than French gamblers. French gamblers more frequently associated a significant win with a positive experience. The common predictors of a significant win experience in both countries were: being in debt, experiencing the win of a close person, gambling in a game of pure chance other than lotteries, more systematic pursuit of gambling, self-enhancement motivation, and coping motivation to gamble. Age at initiation into gambling was a significant predictor only in the French sample, whereas a financial motivation was a significant predictor in the Polish one. The results confirmed that the subjective perception of gambling wins is only partially related to the amounts of wins, which has practical implications for planning prevention strategies.